Transient ischemic attacks: predictability of future ischemic stroke or transient ischemic attack events - Gupta HV; Farrell AM; Mittal MK (Dove Medical Press, 2014)
Harsh V Gupta,1 Ann M Farrell,2 Manoj K Mittal31Department of Neurology, The University of Arkansas Medical Sciences, Little Rock, AR, 2Department of Knowledge and Evaluation Research, Mayo Clinic, Rochester, MN, 3Department of Neurology, The University of Kansas Medical Center, Kansas City, KS, USAAbstract: The short-term risk of an ischemic stroke after a transient ischemic attack (TIA) is estimated to be approximately 3%–10% at 2 days, 5% at 7 days, and 9%–17% at 90 days, depending on active or passive ascertainment of ischemic stroke. Various risk prediction scores are available to identify high-risk patients. We present here a pragmatic review of the literature discussing the main scoring systems. We also provide the sensitivity, specificity, positive predictive value, and negative predictive value for each scoring system. Our review shows that scoring systems including brain imaging and vascular imaging are better at risk prediction than scores that do not include this information.Keywords: ischemic stroke, transient ischemic attack, prediction, systematic review